2017
DOI: 10.1164/rccm.201605-1042oc
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Mycobacterium tuberculosis Strains Share Genetic Markers and Immune Phenotypes

Abstract: Rationale: Successful transmission of tuberculosis depends on the interplay of human behavior, host immune responses, and Mycobacterium tuberculosis virulence factors. Previous studies have been focused on identifying host risk factors associated with increased transmission, but the contribution of specific genetic variations in mycobacterial strains themselves are still unknown.Objectives: To identify mycobacterial genetic markers associated with increased transmissibility and to examine whether these markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Two studies in the Journal offered advances in this field. Nebenzahl-Guimares and colleagues used a tuberculosis registry and strain collection in the Netherlands to identify mycobacterial genetic markers associated with increased transmissibility, and to examine whether these lead to altered in vitro immune responses (40).…”
Section: Transmission Of Tbmentioning
confidence: 99%
“…Two studies in the Journal offered advances in this field. Nebenzahl-Guimares and colleagues used a tuberculosis registry and strain collection in the Netherlands to identify mycobacterial genetic markers associated with increased transmissibility, and to examine whether these lead to altered in vitro immune responses (40).…”
Section: Transmission Of Tbmentioning
confidence: 99%
“…A few prior studies have characterized bacterial genetic factors that contributed to increased transmissibility. 24,27,50 We add to this literature by identifying five cluster defining SNPs to be under positive selection in a large TB genomic dataset. One of these SNPs ( esxV S23L) is a member of the ESAT-6 family of secreted proteins, some of which have been shown to be involved in host-pathogen interactions and may thus have contributed to increased transmissibility.…”
Section: Discussionmentioning
confidence: 99%
“…1820 Factors known to contribute to DR-TB transmission include delays in diagnosis and treatment, 21 host factors like age, and immune status, 22–24 as well as bacterial factors such as fitness and immunogenicity characteristics. 25–27 It is well recognized that Mycobacterium tuberculosis (MTB) strains with the same DR conferring mutations have a range of fitness. 2830 However, to date few molecular fitness determinants have been characterized and seldom in the context of high transmissibility.…”
Section: Introductionmentioning
confidence: 99%
“…Our study had five patients with a particularly high PTP above the highest reported value of 3•9 52 , potentially contributing to transmission in the population we studied. A few prior studies have characterized bacterial genetic factors that contributed to increased transmissibility 24,67,68 . We add to this literature by identifying five cluster defining SNPs to be under positive selection in a large TB genomic dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Factors known to contribute to DR-TB transmission include delays in diagnosis and treatment 21 , host factors (e.g. age, immune status [22][23][24], as well as bacterial factors such as fitness and immunogenicity characteristics [25][26][27] . It is well recognized that Mycobacterium tuberculosis (MTB) strains with the same DR-conferring mutations have a range of fitness [28][29][30] .…”
mentioning
confidence: 99%